Metal chalcogenide thin films. - Zainal, Zulkarnain; Nagalingam, Saravanan; Kassim, Anuar; Hussein, Mohd Zobir; Mat Yunus, Wan Mahmood (2009)

(untitled)
Metal selenide thin film can be produced within five hours by the following method; dissolving selenium in concentrated alkali to form a selenide solution; adding in salt solution of the selected metal to the selenide solution and stirring the resultant solution while metal selenide precipitate; washing the precipitated metal selenide with water to remove excess reactants; drying the washed metal selenide powder; heating the metal selenide powder in a vacuum chamber until metal selenide sublimes and a thin film of the metal selenide is deposited on a clean substrate positioned on the top of the metal selenide powder.